PETA SKEMA ALIANSI PARTAI MENETUKAN AMBANG BATAS UNTUK MEMENANGKAN PASANGAN CALON DALAM PEMILU PRESIDEN DAN WAKIL PRESIDEN TAHUN 2024 (Perbandingan Konseptual dan Mekanisme dengan Teori Sikap Politik): - , Via Amanda; Eka Yulyana (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2024)
The threshold thatdetermines by obtaining "20% of seats in the DPR or at least 25% of the votes in the general election" is based on a comparison of the Constitutional Court Decision of the Republic of Indonesia 59 / PUU-XV / 2017 with Paragraph 1 of Article 222 of Law Number 7 of 2017 which can affect the political attitude of the community that can encourage the alliance of young parties to reach the threshold requirement. This research is to understand policies that affect people's attitudes and participation as one of the requirements in the presidential threshold.  The research method used is a literature study based on political attitude theory. The results of this discussion represent the problem of determining the threshold for a new party coalition ahead of the general election. There are reconstructive views that can serve as a threshold strategy for party alliances. In conclusion, there is no valid threshold decision, so the party alliance has the right to nominate a pair of candidates and it depends on the attitude of voters as political parties who support the spouses in the party.